Техника и технология добычи руд за рубежом - Подвишенский С. Н. Станислав Николаевич; Иофин С. Л. Станислав Леонидович; Ивановский Э. С. Энгель Сергеевич; Гальперин В. Г. Владимир Григорьевич (Москва, Недра, 1986)
Авт. указаны на обороте тит. л.